QUALIDADE DAS SEMENTES DE CULTIVARES DE MILHO CRIOULAS ARMAZENADAS NO CAMPO NA REGIÃO DOS CAMPOS GERAIS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
corn seeds stored in the field after physiological maturity. The seeds of variety Mogiana were collected in the crop Reserva Municipality - PR, while the seeds of variety Cunha were collected in the city of Teixeira Soares - PR. For each variety were carried out six collections composed of 15 spikes with intervals between eight and 36 days. We analyzed the number of seeds per ear, thousand seed mass, protein content, germination at four and seven days after germination cold stress, seedling length and determining the presence of fungi. The experimental design was completely randomized, six treatments (harvest time) and four replications. It was observed that occurred mass increase of thousand seeds during storage field. The physiological characteristics of the variety Cunha were lower than the variety Mogiana and tended to decrease over the period of maintenance of the plants in the field. There was no significant difference in protein in both cultivars. Germination at four and seven days after germination stress cold and seedling length for Mogiana and Cunha varieties averaged 94.70 and 87.30%, 96.70% and 89.50, 91.14 and 73 11%, 12.95 and 13.93 cm, respectively. There was a positive correlation of germination at four and seven days of the variety Mogiana, and there was no significant difference for germination after stress by cold and length of seedling with the evolution of harvest time. There was a negative correlation of the physiological characteristics of Cunha seeds with the evolution of harvest time, except for length of seedlings which showed a positive correlation. The Mogiana and Cunha varieties showed high contamination by Penicillium spp., Fusarium spp low. and negligible values for Aspergillus spp., Diplodia spp. and Rhizopus spp. For the two varieties was negative correlation between the occurrence of Penicillium spp. with the evolution of harvest time. For variety, Cunha occurred positive correlation of the occurrence of Fusarium spp. with the evolution of the harvest period and opposite behavior to seed Mogiana.
Seed quality of creole maize cultivars stored in the field in the region of general fields
Keywords: Zea mays L.; Mogiana; Cunha; germinação; sanidade; Zea mays L.; Mogiana; Cunha; germination; sanity; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA